Synthesis and Application of New Ruthenium Complexes Containing β-Diketonato Ligands as Sensitizers for Nanocrystalline TiO2 Solar Cells. (7th June 2011) - Islam, Ashraful; Singh, Surya Prakash; Han, Liyuan
Abstract : Five heteroleptic ruthenium complexes having different β -diketonato ligands, [Ru(tctpy)(dppd)(NCS)] (1 ), [Ru(tctpy)(pd)(NCS)] (2 ), [Ru(tctpy)(tdd)(NCS)] (3 ), [Ru(tctpy)(mepd)(NCS)] (4 ), and [Ru(tctpy)(tmhd)(NCS)] (5 ), where tctpy = 4, 4′, 4′′-tricarboxy-2, 2′:6′, 2′′-terpyridine, pd = pentane-2, 4-dione, mepd = 3-methylpentane-2, 4-dione, tmhd = 2, 2, 6, 6-tetramethylheptane-3, 5-dione, tdd = tridecane-6, 8-dione, and dppd = 1, 3-diphenylpropane-1, 3-dione, were synthesized and characterized. These heteroleptic complexes exhibit a broad metal-to-ligand charge transfer absorption band over the whole visible range extending up to 950 nm. The low-energy absorption bands and the E (Ru 3+/2+ ) oxidation potentials in these complexes could be tuned to about 15 nm and 110 mV, respectively, by choosing appropriate β -diketonate ligands. Molecular orbital calculation of complex1 shows that the HOMO is localized on the NCS ligand and the LUMO is localized on the tctpy ligand, which is anchored to the TiO2 nanoparticles. The β -diketonato-ruthenium(II)-polypyridyl sensitizers, when anchored to nanocrystalline TiO2 films for light to electrical energy conversion in regenerative photoelectrochemical cells, achieve efficient sensitization to TiO2 electrodes with increasing activity in the order5 <4 <3 ≈ 2 <1 . Under standard AM 1.5 sunlight, the complex1 yielded a short-circuit photocurrent density of 16.7 mA/cm 2, an open-circuit voltage of 0.58 V, and a fill factor of 0.64, corresponding to an overall conversion efficiency of 6.2%. A systematic tuning of HOMO energy level shows that an efficient sensitizer should possess a ground-state redox potential value of >+.53 V versus SCE.